2006
DOI: 10.1590/s0103-84782006000500003
|View full text |Cite
|
Sign up to set email alerts
|

Controle químico da ferrugem asiática da soja em função de ponta de pulverização e de volume de calda

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
18

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 3 publications
1
17
0
18
Order By: Relevance
“…Gotas finas podem aumentar a cobertura em pulverizações e com isto a eficácia dos produtos (Derksen et al, 2007). Gotas grossas são menos propensas à evaporação e carreamento pelo vento sendo, porém, mais sujeitas a não se fixarem no alvo e escorrerem para o solo (Cunha et al, 2006;Czaczyk et al, 2012).…”
Section: Introductionunclassified
“…Gotas finas podem aumentar a cobertura em pulverizações e com isto a eficácia dos produtos (Derksen et al, 2007). Gotas grossas são menos propensas à evaporação e carreamento pelo vento sendo, porém, mais sujeitas a não se fixarem no alvo e escorrerem para o solo (Cunha et al, 2006;Czaczyk et al, 2012).…”
Section: Introductionunclassified
“…Recentemente, vários trabalhos têm sido desenvolvidos analisando o desempenho de pontas de pulverização associadas à redução de volumes de calda, buscando melhorias na capacidade de trabalho e rendimento operacional das aplicações no controle de pragas e doenças, na cultura da soja em estádios reprodutivos. Entretanto, o aprimoramento da tecnologia de aplicação visando a reduzir o volume de calda tem como consequência negativa a diminuição da cobertura adequada do alvo desejado, principalmente nas partes inferiores da cultura (SCUDELER et al, 2004;CUNHA et al, 2006;CUNHA et al, 2008;BOSCHINI et al, 2008;FARINHA et al, 2009a;NASCIMENTO et al, 2009;BAUER et al, 2009;CUNHA & PERES, 2010;CHRISTOVAM et al, 2010a, b).…”
unclassified
“…The authors verified that very fine quality spray obtained with hollow cone TX VK6 nozzle and Twinjet flat fan TJ 60 11002 nozzle, and fine quality spray with a flat fan pattern XR 11002 nozzle, provided greater coverage in middle and bottom parts of the soybean plants when compared to the extremely coarse spray quality produced by air induction flat fan nozzles. The effects of spray nozzles (flat fan pattern, pre-orifice flat fan, air induction flat fan and air induction twin flat fan) and volume rates (115 and 160 L ha -1 ) on chemical control of rust and the deposition of tebuconazole fungicide sprayed on soybeans of the Emgopa 313 variety, were studied by Cunha et al (2006). The results showed that, despite the fact of the volume rate of 160 L ha -1 and of the use of pattern flat fan nozzles, they provided larger fungicide distribution uniformity in the plant canopy.…”
Section: Droplet Categorymentioning
confidence: 99%